Spatial distribution of the sand-dwelling fish Gymnorhamphichthys rondoni in a neotropical terra firme stream (2018)
Weakly electric fish constantly emit Electric Organ Discharges (EOD) as means of communication and localization. Water conductivity affects the electrocommunication in these fish by increasing its range when water conductivity is low. Therefore, we investigated the effect of water conductivity on the choosing resting places by the sand-dwelling fish Gymnorhamphichthys rondoni in a terra firme stream known as Yahuarcaca in Leticia Amazonas. This stream is also a nutrient deficient habitat, therefore we explored in addition if this condition may affect EOD frequency discharge rates at rest in G. rondoni individuals. Through five field trips to the sampling site Y4 within this stream we recorded some physicochemical parameters such as water conductivity, and the distribution of G. rondoni individuals. Also, we recorded the EODs of the two closest individuals found throughout the day and night, including the time leaving and returning to their hiding sites. We found that most of the physicochemical parameters did not change...